2015
DOI: 10.12693/aphyspola.128.b-110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Neutronic Calculations of Certain Alternative Fuels in a Boiling Water Reactor by Using MCNPX Monte Carlo Method

Abstract: We were studying on the modeling of boiling water reactor fuel assemblies at pin-by-pin level by using Monte Carlo method. The designed boiling water reactor system is cylinder, and the radius of the cylinder is 228 cm. The total active core height is 315.79 cm. The reactor core was divided into the square lattice 7 × 7 type with a constant pitch of 30 cm. The core was surrounded with the reflector. The reflector was surrounded by SS316LN ferritic steel with width of 3 cm. The mixtures 0.2−1% PuF4 and PuO2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The pin cell geometry in the small square lattice of the designed BWR system is shown in Fig. 3 19 . 49 fuel rods inside every small square lattice and 196 fuel rods inside every square lattice were placed in the designed BWR system.…”
Section: Methodsmentioning
confidence: 99%
“…The pin cell geometry in the small square lattice of the designed BWR system is shown in Fig. 3 19 . 49 fuel rods inside every small square lattice and 196 fuel rods inside every square lattice were placed in the designed BWR system.…”
Section: Methodsmentioning
confidence: 99%
“…2, we can see the trajectory and interaction volume of X-rays in a sample. Various simulation investigations and estimation studies on medical applications and for other aims such as computational methods are found in literature [7][8][9][10][11][12][13][14][15][16][17][18][19]. A schematic representation of modelled geometry is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The gap had a width of 0.01524 cm in between the fuel rod and the clad. The pin cell geometry in the small square lattice of the designed BWR system is shown in Figure 3 (Günay et al, 2015).…”
Section: Geometry Descriptionmentioning
confidence: 99%